Cash-on-Delivery (COD) Umrah Financing in Islamic Financial Institutions: A Sharia Economic Law Analysis - Syawaluddin Ismail; Muhammad Firdaus (International Journal of Sharia Studies, 2026)
Ideally, Umrah financing provided by Islamic financial institutions should be implemented based on the principles of justice, contractual certainty, and compliance with Islamic economic law. In practice, however, the emergence of the Cash on Delivery (COD) scheme in Umrah financing has raised legal concerns regarding the validity of contracts, the timing of benefit delivery, risk allocation, and the protection of the parties involved. This study aims to examine the legal validity of COD-based Umrah financing from the perspective of Islamic economic law. This research employs a qualitative library research design using a normative legal approach through statutory, conceptual, and case approaches. Primary sources include the Qur'an, Hadith, fatwas issued by the National Sharia Council–Indonesian Council of Ulama (DSN-MUI), and relevant legislation, while secondary sources consist of scholarly books and peer-reviewed journal articles. The data were analyzed using content analysis and prescriptive legal analysis. The findings indicate that COD-based Umrah financing is legally valid under Islamic economic law provided that it fulfills the essential elements and conditions of the contract, is free from riba, gharar, and maysir, and ensures certainty in benefit delivery, transparency, and equitable risk allocation. Strengthening contractual design and Sharia compliance is essential to ensure that this financing model remains aligned with the objectives of Maqāṣid al-Sharīʿah, consumer protection, and legal certainty.